PRACTICE OF ANIMALS TRADING IN ISLAMIC LAW & POSITIVE LAW OF BIOLOGICAL RESOURCES & ITS ECOSYSTEMS - As'ari Taufiqurrohman; Ong Argo Victoria; Nur Fareha Binti Mohamad Zukri (International Journal of Law Society Services, 2021)
Indonesia is a country that is very rich in the diversity of its natural resources. Both in terms of flora and fauna. However, Indonesia is an emerging country for the circulation of endangered animals that have been protected by law. The Animal Market is one of the places where several protected animals are circulated. In this study, the authors found a unique incident in the practice of buying and selling endangered animals that have been protected by this law, where the practice of buying and selling rare animals is carried out in markets managed by the government, namely under the auspices of the Department of Agriculture, Fisheries and Food. The focus of this research is to find out how the practice of buying and selling endangered animals in the Animal Market and how the review of Islamic law and Act No. 5 of 1990 concerning the Conservation of Biological Natural Resources and Their Ecosystems. Through qualitative research methods and through a juridical normative approach, the researcher tries to uncover the focus of the problem above by going directly to the field to find facts which then leads to an analysis of Islamic law and Act No. 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems. Data were taken through documentation, observation, and interviews. The data that has been obtained is presented in the form of a description in order to obtain conclusions. The results of the study explain that the sale and purchase of endangered animals protected under Islamic law is a sale that does not bring benefits, contains najis, does not belong to the seller wholly, causes damage to nature, and contains fraud. Meanwhile, when viewed from Act No. 5 of 1990 concerning the Conservation of Natural Resources and Their Ecosystems, the practice of buying and selling endangered animals that are protected illegally is a criminal act of wildlife crime in which the legal consequences of this crime are a maximum criminal sanction of ten years in prison and a fine of between 100 million and IDR 200 million rupiahs.